Diversity of Vascular Plants in Deciduous Dipterocarp Forest at Thammasat University, Lampang Campus, Lampang Province, Thailand - Janejaree Inuthai (Science & Technology Asia, 2021)
A study on the species diversity of vascular plants was carried out in the deciduous dipterocarp forest at Thammasat University, Lampang Campus, Lampang Province from November 2018 to October 2019. One hundred and twenty- one plant species, belonging to 45 families and 99 genera were documented, which included 16 exotic species. The three most commonly encountered families were Fabaceae (23 species), Malvaceae (9 species), and Convolvulaceae (8 species). The most diverse species were Cratoxylum cochinchinense, C. formosum subsp. pruniflorum, Dipterocarpus obtusifolius, D. tuberculatus, and Garcinia nigrolineata. A schematic profile of the vegetation with three layers was illustrated. Abundance, habits, and habitats were recorded. Flowering and fruiting phenology of each species was observed. Concerning species conservation, the remnant forests on the campus should be conserved and revitalized, as well as used as a natural learning center of the University, before the inhabiting species permanently disappear.